2019
DOI: 10.22335/rlct.v4i1.179
|View full text |Cite
|
Sign up to set email alerts
|

Causas psicosociales de la deserción universitaria

Abstract: entre el 2009 y 2011. De un total de 65 personas, la muestra fue de 16 personas que cumplían con los criterios de selección. Se revisó la información existente en la Institución acerca de las pruebas MMPI y RAVEN, las pruebas saber 11, aspectos financieros, familiares y académicos. Los

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…En síntesis, apostar por estimular y fomentar el concepto de paz(es) en el contexto de la educación superior involucra alternativas de pacificación en una sociedad crítica, reflexiva, con esperanzas. (Reyes Ruiz, et al, 2012) Otro aspecto interesante tiene que ver con lo pedagógico. Al respecto, Madrigal (2020) propone cuatro dimensiones interdependientes de la educación para la paz:…”
Section: De Los Principios Reguladores Para Un Currículo Que Fomenta ...unclassified
“…En síntesis, apostar por estimular y fomentar el concepto de paz(es) en el contexto de la educación superior involucra alternativas de pacificación en una sociedad crítica, reflexiva, con esperanzas. (Reyes Ruiz, et al, 2012) Otro aspecto interesante tiene que ver con lo pedagógico. Al respecto, Madrigal (2020) propone cuatro dimensiones interdependientes de la educación para la paz:…”
Section: De Los Principios Reguladores Para Un Currículo Que Fomenta ...unclassified
“…Similarly, the study counseling and support program was identified, in learning strategies and psychological support as a program used by universities in order to increase the retention and academic performance of students (Cabrera et al, 2006). This contribution includes an added value and it is the consideration of psychological support within retention strategies for students, which leads to infer about the relevance of making the relationship between the variables of dropout and psychological support, which in turn allows accompany and intervene in students relevant aspects such as stress, related to unhealthy behaviors (Riveros, Rubio, Candelario, & Magín, 2013;Reyes, Castañeda, & Pabón, 2012). Likewise, pregnancy, depression, dysfunctional or disintegrated family, lack of communication, addictions, low moods, among others, have been identified; as factors that influence academic performance and dropout (Cruz, Barrientos, García, & Hernández, 2010).…”
Section: Introductionmentioning
confidence: 99%